Cultura organizacional y su relación con los sistemas de gestión: Una revisión bibliográfica (2021)
Management systems promote the organizational culture development within the organization orientated towards continuous improvement. Therefore, it is relevant to apply planned and directed individual and collective change processes to develop good performance practices that make functions management efficient and effective. This study shows a literature review of the definitions and essential ideas about the transformation, maintenance and diagnosis of the organizational culture. A description and juxtaposition of the information is made as a comparative structure based on ISO 9000 and ISO 9001 technical standards, academic documents and various authors. This allows the analysis, identification and classification of the most significant dimensions related to the organizational culture and that affect adaptation and integration thereof. The comparative study gathers and aligns the different theoretical references analyzed and related to quality principles, and results in the synthesis of the dimensions requiring greater intervention and that can be incorporated into the organizational culture.